Quantum Biology: The Interaction of Quantum Mechanics in Biological Systems - Dorji Phuntsho; Pema Lhamo; Omar Ahmad (Journal of Tecnologia Quantica, 2025)
Research Background: Quantum Biology is a branch of science that studies the interaction between quantum mechanics and biological systems. Some early studies have shown that quantum phenomena affect the efficiency of biological processes, but understanding of their applications is still limited. Research Objectives: This study aims to investigate how quantum mechanics plays a role in biological processes, especially in photosynthesis and magnetic navigation in migratory birds. Research Methods: This research uses laboratory experiments with an interdisciplinary approach, combining quantum physics and molecular biology techniques. The samples used included plant culture cells and migratory birds, as well as data analysis using mathematical modeling to describe quantum phenomena in biological systems. Research Results: The results show that quantum phenomena, such as coherence and entanglement, play a role in improving the efficiency of photosynthesis and the ability of birds to navigate based on the Earth's magnetic field. The study also identified a quantum mechanism that accelerates metabolic processes in cells. Research Conclusions: This study provides strong evidence that quantum mechanics can directly affect biological systems. These findings open up opportunities for the development of quantum-based biotechnology, as well as provide new insights into understanding more efficient and coordinated biological processes.